Effect of temperature cycles on the sleep-like state in Hydra vulgaris - Aya Sato; Manabu Sekiguchi; Koga Nakada; Taishi Yoshii; Taichi Q. Itoh (Zoological Letters)
Abstract Background Sleep is a conserved physiological phenomenon across species. It is mainly controlled by two processes: a circadian clock that regulates the timing of sleep and a homeostat that regulates the sleep drive. Even cnidarians, such as Hydra and jellyfish, which lack a brain, display sleep-like states. However, the manner in which environmental cues affect sleep-like states in these organisms remains unknown. In the present study, we investigated the effects of light and temperature cycles on the sleep-like state in Hydra vulgaris. Results Our findings indicate that Hydra responds to temperature cycles with a difference of up to 5° C, resulting in decreased sleep duration under light conditions and increased sleep duration in dark conditions. Furthermore, our results reveal that Hydra prioritizes temperature changes over light as an environmental cue. Additionally, our body resection experiments show tissue-specific responsiveness in the generation ofthe sleep-like state under different environmental cues. Specifically, the upper body can generate the sleep-like state in response to a single environmental cue. In contrast, the lower body did not respond to 12-h light–dark cycles at a constant temperature. Conclusions These findings indicate that both light and temperature influence the regulation of the sleep-like state in Hydra. Moreover, these observations highlight the existence of distinct regulatory mechanisms that govern patterns of the sleep-like state in brainless organisms, suggesting the potential involvement of specific regions for responsiveness of environmental cues for regulation of the sleep-like state.